Factors that affect the English language teaching-learning process in Ecuadorian private high schools 2015. - Loján Loján, Karla Elizabeth (2015)
The present study investigated the factors that affect the English language teaching-learning process in Ecuadorian private high schools. This research was conducted in five randomly selected private high schools located in the city of Loja. In those institutions, fifteen English teachers and fifteen students were surveyed by means of a questionnaire. Furthermore, the fifteen teachers had to be interviewed and the same number of classes had to be monitored. The analysis of the collected data was done in a quantitative and qualitative way. In this analysis, it was necessary to consider factors concerning teachers, students, classrooms, and educational institutions. The most important conclusion reveals that one of the factors which affect the English teaching-learning process is that not all the teachers have an English Bachelor degree because a teacher who only has a High School Diploma in their classroom shows a lack of knowledge in educational methods.